Temperature affects N and C assimilation and translocation in Curcuma alismatifolia Gagnep - T. Khuankaew (2018)
Curcuma alismatifolia has become popular as an ornamental plant because of its colourful, long-lasting, and repeated growth of inflorescences. The effects of temperature on N and C assimilation and transport during the initial flowering stage were investigated using 15 N and 13 C. Treatments at 15°C, 25°C, or 35°C had no significant effect on total 15 N absorption by the plants. However, the distribution of 15 N was affected by temperature. The concentration of 15 N in new rhizomes and leaves was lower at 15°C than at 25°C, although the concentrations of 15 N in old rhizomes and old storage roots were higher. The concentration of 15 N in roots and leaves was lower at 35°C than at 25°C.Total plant 13C concentrations were highest at 25°C, followed by 15°C, and lowest at 35°C. The concentration of 13 C in new rhizomes was the highest, followed by leaves and inflorescences at 25°C. The concentrations and distribution of 13 C in new rhizomes and in new storage roots were highest at 25°C. These results indicate that temperature regulates the assimilation and transport of N and C, with the optimum temperature being between 25° - 35°C.